(untitled) (AYUSHDHARA, 2025)
Madhumeha, one of the twenty types of Prameha described in Ayurveda. It is a chronic metabolic disorder characterized by impaired carbohydrate, fat, and protein metabolism leading to hyperglycemia and multiple systemic complications. Classical Ayurvedic texts emphasize the role of Shodhana Chikitsa (purificatory therapies) in the management of Madhumeha to correct the deranged Doshas and to improve Agni and Srotoshuddhi. Among these, Nitya Virechana (daily purgation) is considered effective for eliminating vitiated Pitta and Kapha while regulating Apana Vata. This case report presents the management of a 44-year-old male patient diagnosed with Madhumeha who exhibited classical clinical features such as Prabhuta Mutrata (polyuria), Naktamutrata (nocturia), Vibandha (constipation), Atinidra (excessive sleep), Swedadhikya (excessive sweating), Daurbalya (weakness), Kshudhadhikya (polyphagia), and Karapada Daha (burning sensation in palms and soles). The patient was administered Nitya Virechana with Trivrit Kwatha (decoction of Operculina turpethum) daily for 21 days. Regular clinical monitoring and assessment of glycemic parameters were carried out during the intervention period. At the end of therapy, the patient demonstrated significant improvement in glycemic control along with marked relief from associated symptoms such as constipation, excessive sleep, weakness, and burning sensation. The therapy was well tolerated without adverse effects. This case highlights the potential role of Nitya Virechana with Trivrit Kwatha as an effective supportive Ayurvedic intervention in the management of Madhumeha. It emphasizes the importance of Ayurvedic Shodhana measures in addressing the metabolic derangements of diabetes and improving quality of life.